1998
DOI: 10.1074/jbc.273.9.5190
|View full text |Cite
|
Sign up to set email alerts
|

Expression Cloning of a Human Sulfotransferase That Directs the Synthesis of the HNK-1 Glycan on the Neural Cell Adhesion Molecule and Glycolipids

Abstract: The HNK-1 carbohydrate is expressed on various adhesion molecules in the nervous system and is suggested to play a role in cell-cell and cell-substratum interactions. Here we describe the isolation and functional expression of a cDNA encoding a human sulfotransferase that synthesizes the HNK-1 carbohydrate epitope. A mutant Chinese hamster ovary cell line, Lec2, which stably expresses human neural cell adhesion molecule (N-CAM) (Lec2-NCAM), was first established. Lec2-NCAM was co-transfected with a human fetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
107
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 44 publications
(40 reference statements)
4
107
0
2
Order By: Relevance
“…This is compatible with the finding that GalNAc transferase catalyzing chondroitin chain elongation cannot transfer GalNAc to 3-O-sulfated GlcA (30). This sulfation may be accomplished either with a similar sulfotransferase, as reported for the detection of SO 4 -3GlcA␤1-4Xyl␤-4-methylumbelliferone from the substrate, 4-methylumbelliferyl ␤-Xyl (31), or with the sulfotransferase involved in the biosynthesis of the HNK-1 carbohydrate epitope (32,33). These results suggest that glycosaminoglycan chain elongation of human TM seems to be abolished at the linkage tetrasaccharide core structure by addition of a sulfate group, indicating that 3-O-sulfation is a stop signal leading to TM lacking chondroitin sulfate.…”
Section: Discussionsupporting
confidence: 70%
“…This is compatible with the finding that GalNAc transferase catalyzing chondroitin chain elongation cannot transfer GalNAc to 3-O-sulfated GlcA (30). This sulfation may be accomplished either with a similar sulfotransferase, as reported for the detection of SO 4 -3GlcA␤1-4Xyl␤-4-methylumbelliferone from the substrate, 4-methylumbelliferyl ␤-Xyl (31), or with the sulfotransferase involved in the biosynthesis of the HNK-1 carbohydrate epitope (32,33). These results suggest that glycosaminoglycan chain elongation of human TM seems to be abolished at the linkage tetrasaccharide core structure by addition of a sulfate group, indicating that 3-O-sulfation is a stop signal leading to TM lacking chondroitin sulfate.…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, GlcAT-I seems to be mainly involved in the biosynthesis of the GAG-protein linkage region of proteoglycans. However, based on the present ¢ndings that the transfection of GlcAT-I cDNA into COS-1 cells induced a signi¢cant expression of the HNK-1 epitope, it is possible that tissues which abundantly express the GlcAT-I gene synthesize the HNK-1 epitope GlcA(3-O-sulfate)L1-3GalL1-4GlcNAc, especially since the HNK-1 3-O-sulfotransferase is widely distributed in various tissues and GlcAT-P most likely regulates the expression of the HNK-1 epitope [18,19]. In accordance with this suggestion, Wei et al recently reported the expression of the HNK-1 epitope in GlcAT-I cDNA-transfected COS-7 and Lec 2 cells when cotransfected with the HNK-1 3-O-sulfotransferase [14].…”
Section: Acceptormentioning
confidence: 99%
“…The GalNAc-sulfotransferases add sulfate to the C4 hydroxyl of either terminal ␤1,4-linked GalNAc (GalNAc-4-ST1 (3,5) and GalNAc-4-ST2 (6)) or to ␤1,4-linked GalNAc that is substituted at its C-3 hydroxyl with either GlcUA (C4ST-1 (8, 9) and C4ST-3) or IdoUA (D4ST-1 (7)). In contrast, HNK-1 ST adds sulfate to the C-3 hydroxyl of terminal ␤1,3-linked GlcUA (1,2). Each member of this family of sulfotransferases is thus highly specific, and the unique sulfated structures that are produced have distinct biological roles.…”
Section: Chrondroitin-4-sulfotransferase-3mentioning
confidence: 99%